Efektifitas Bimbingan Kelompok Teknik Homeroom Untuk Mengurangi Perilaku Bullying Pada Remaja - Nur Fadila Dewi Saputri; Muhammad Sholihuddin Zuhdi (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
This research is motivated by the many bullying behaviors in schools, bullying is a desire to hurt someone. In addition, this study was conducted with the aim of testing the effectiveness of group guidance with the homeroom technique in reducing student bullying behavior before and after being given treatment (experiment). This research uses quantitative research methods. This research is a pre experimental design using one group design pretest-posttest design because this design is designed to compare a treatment. In this study, quantitative data were obtained from a questionnaire instrument or a revealing questionnaire of 3.3% bullying behavior. The population in this study were 240 students of class XI MAN Blitar City. The sampling technique used purposive sampling, so that the sample of this study amounted to 8 students. The data analysis technique used is the t-test pired sample t-test. The results of this study indicate that a significant value of 0.000 0.05 means that H0 is rejected. Ha is accepted, that is, after group guidance with the homeroom technique is carried out, bullying behavior decreases. This means that group guidance is effective in overcoming bullying behavior in students at MAN Kota Blitar. The conclusion of this research is group guidance with the homeroom technique is effective to overcome the bullying behavior of students of Class XI MAN Kota Blitar.